2014
DOI: 10.1080/01635581.2014.884232
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Adverse Effects by a Mushroom Product, Active Hexose Correlated Compound (AHCC) in Patients With Advanced Cancer During Chemotherapy—The Significance of the Levels of HHV-6 DNA in Saliva as a Surrogate Biomarker During Chemotherapy

Abstract: Chemotherapy improves the outcome of cancer treatment, but patients are sometimes forced to discontinue chemotherapy or drop out of a clinical trial due to adverse effects, such as gastrointestinal disturbances and suppression of bone marrow function. The objective of this study was to evaluate the safety and effectiveness of a mushroom product, active hexose correlated compound (AHCC), on chemotherapy-induced adverse effects and quality of life (QOL) in patients with cancer. Twenty-four patients with cancer r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 25 publications
0
23
1
Order By: Relevance
“…Findings indicated increased QOL and decreased human herpesvirus 6 in saliva [6]. In another study, AHCC (3 g/d) was administered to 18 breast cancer patients who were receiving chemotherapy (Anthracycline and Taxane) and results were compared to 23 patients who did not receive AHCC.…”
Section: Discussionmentioning
confidence: 99%
“…Findings indicated increased QOL and decreased human herpesvirus 6 in saliva [6]. In another study, AHCC (3 g/d) was administered to 18 breast cancer patients who were receiving chemotherapy (Anthracycline and Taxane) and results were compared to 23 patients who did not receive AHCC.…”
Section: Discussionmentioning
confidence: 99%
“…Integrative Cancer Therapies 15 (1) and concluded that mouthwashes (used to thoroughly rinse the oral cavity for 5 minutes and then swallowed immediately) containing vitamin E did not affect the survival rate of patients with cancer of the oral cavity and oropharynx. In addition, they reported that the supplementation reduced the incidence of mucosal adverse effects during radiotherapy.…”
Section: Conducted a Double-blind And Placebo-controlled Rctmentioning
confidence: 99%
“…Integrative Cancer Therapies 15 (1) and tumor progression, should be determined and the results disseminated widely. In this study, we reviewed antioxidants as an adjuvant therapy for cancer patients during chemotherapy or radiotherapy.…”
Section: Research-article2015mentioning
confidence: 99%
See 1 more Smart Citation
“…diseases, and is a cancer therapy [26][27][28][29][30][31][32]. The safety of AHCC has been supported by basic studies, including its interaction with drugs [33][34][35].…”
Section: Ph Lps Ahccmentioning
confidence: 99%